Grapsoid crabs (Decapoda: Brachyura: Thoracotremata) of the Persian Gulf and the Gulf of Oman - Naderloo, Reza (Zootaxa, 2011)
Grapsoid crabs, together with ocypodoids, are the two most important groups of intertidal brachyurans in the Persian Gulf and the Gulf of Oman. In total, four families, nine genera and 12 species of grapsoids are known from the region. Perisesarma guttatum (A. Milne-Edwards, 1869), and Plagusia squamosa (Herbst, 1790), are only recorded from the Gulf of Oman; Grapsus granulosus H. Milne-Edwards, 1853, and Thalassograpsus harpax (Hilgendorf, 1892), are collected for the first time from the Persian Gulf. Chiromantes boulengeri (Calman, 1920), Nanosesarma sarii Naderloo & Türkay, 2009, and Parasesarma persicum Naderloo & Schubart, 2010, are so far known only from the region.